2005
DOI: 10.1158/1078-0432.ccr-04-2446
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum DNA GSTP1 CpG Island Hypermethylation and the Risk of Early Prostate-Specific Antigen Recurrence Following Radical Prostatectomy

Abstract: Purpose: Hypermethylation of the CpG island at the promoter region of the P-class glutathione S-transferase gene (GSTP1) is the most common somatic genome abnormality in human prostate cancer. We evaluated circulating cell-free DNA GSTP1 CpG island hypermethylation as a prognostic biomarker in the serum of men with prostate cancer. Experimental Design: Prostate cancer DNA GSTP1 CpG island hypermethylation was detected using a restriction endonuclease quantitative PCR technique. We analyzed preoperative serum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
120
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 38 publications
(25 reference statements)
3
120
2
Order By: Relevance
“…Our hypermethylation frequency of GSTP1 was somewhat higher than those reported by other groups [12][13][14][15]18]. These differences maybe explained by different detection methods and/or differences in the study cohort: Bastian et al used also a restriction endonuclease method and detected GSTP1 hypermethylation in 12% of serum samples from PCA patients in a screening cohort with US-Americans.…”
Section: Discussioncontrasting
confidence: 71%
“…Our hypermethylation frequency of GSTP1 was somewhat higher than those reported by other groups [12][13][14][15]18]. These differences maybe explained by different detection methods and/or differences in the study cohort: Bastian et al used also a restriction endonuclease method and detected GSTP1 hypermethylation in 12% of serum samples from PCA patients in a screening cohort with US-Americans.…”
Section: Discussioncontrasting
confidence: 71%
“…5 In that study we observed that CpG island hypermethylation at GSTP1 predicted early PSA recurrence following radical prostatectomy. Of all men with clinically localized disease those with a positive test for DNA GSTP1 CpG island hypermethylation were at 4.4 times greater risk for biochemical relapse than those with a negative test.…”
Section: Discussionmentioning
confidence: 83%
“…The results of GSTP1 hypermethylation were included from our previous investigation. 5 The percent of patients with DNA hypermethylation were compared in each group. Because the 4 groups represented worsening disease categories, the percent with DNA hypermethylation was evaluated for a linear trend, ie whether the percent that was methylated increased with each worsening category.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the Ibragimova et al study is its lack of testing in body fluids (plasma and/or urine), where detection of CpG island hypermethylation could have a clear clinical value (14) and would add to the novelty of the findings. It also would be important to extend the number of specimens in the tissue validation set to ascertain whether all PIN lesions indeed are unmethylated at the TACSTD2 promoter.…”
mentioning
confidence: 99%